PENGEMBANGAN MODUL PEMBELAJARAN FISIKA BERNUANSA PENDIDIKAN ISLAM DI SMA ISLAM AL AZHAR 12 MAKASSAR - Nur Thahirah Umajjah Irha (IAI Al-Mawaddah Warrahmah Kolaka, 2018)
This research aims to: (1) develop the learning module of physics nuance of Islamic education for the students of class XI in SMA Islam Al Azhar 12 Makassar in terms of theoretical validity, (2) develop the learning module of physics nuances of Islamic education for the students of class XI in SMA Islam Al -Azhar 12 Makassar in terms of empirical validity (3) describes the development profile of physics learning module nuanced Islamic education for students of class XI in SMA Islam Al-Azhar 12 Makassar. The type of research used is development research with 3D development model that meruapakan adaptation of 4D development model. The test subject in this research is 20 students kelsi XI IPA SMA Islam Al Azhar 12 makassar. The result of the research shows that (1) Theoretical validity of physics learning module with nuance of Islamic education with expert validity method is in valid category, by using Gregory test, consistent internal level (reliability) of learning module is very consistent that is 100%. While the validity of theoretical with the method of face validity, physics learning module nuanced Islamic education is in the right category in measuring indicators, clear in the use of language, and both in terms of kegrafikan, (2) Results analysis of the learners showed that 35% Learners judge that the learning module is in good category and 65% category is very good. Results of response analysis Learners for each item statement indicates that 100% Learners respond positively to at least 50% statement items. So it can be concluded that physics learning module nuanced Islamic education can be used with small resvisi.Hasil empirical validity also indicate the interest of large learners in the process of learning physics by using the module, especially with material integrated with the Qur'an, (3 ) The final profile of physics learning module nuanced in Islamic education class XI developed in SMA Islam Al Azhar 12 Makassar are: (1) Cover, (2) Preface, (3) Table of contents,, (4) Introduction, (5) Concept Map, (8) Teaching materials, (9) Self-training, (10) Student worksheet (LKPD), (11) Glossary, (12) Formative test. (13) Key answers formative test form description, (14) Test results cognitive learning. (15) Key answers to test results of cognitive learning. Test results of cognitive learning along with key answers are not contained in the module, because the test is only owned by subject teachers.